Elevated lipoprotein(a), hypertension and renal insufficiency as predictors of coronary artery disease in patients with genetically confirmed heterozygous familial hypercholesterolemia. (15th December 2015) - Chan, Dick C.; Pang, Jing; Hooper, Amanda J.; Burnett, John R.; Bell, Damon A.; Bates, Timothy R.; van Bockxmeer, Frank M.; Watts, Gerald F.
Abstract: Background: Familial hypercholesterolemia (FH) is characterized by elevated LDL-cholesterol and increased risk of premature coronary artery disease (CAD). Lipoprotein(a) [Lp(a)] increases CAD in FH, although the independence of this association relative to other CAD risk factors remains unclear. In this study, we examined the association between Lp(a) and other cardiovascular risk factors and prevalent CAD in patients with FH. Methods: A cross-sectional study of 390 patients with genetically confirmed FH were studied. Clinical and biochemical parameters of FH patients with and without CAD were compared. Results: FH patients with CAD were older and more often male and had a higher prevalence of hypertension, smoking, diabetes, obesity, reduced eGFR, and elevated plasma Lp(a) and pre-treatment LDL-cholesterol and triglyceride (or low HDL-cholesterol) than FH patients without CAD ( P < 0.05 for all). In univariate analyses, age, male gender, smoking, hypertension, reduced eGFR, diabetes, obesity, plasma creatinine, Lp(a) and pretreatment LDL-cholesterol, triglycerides and HDL-cholesterol levels were significant predictors of CAD in the FH patients ( P < 0.05 for all). Elevated LDL-cholesterol, raised Lp(a), hypertension and reduced eGFR remained significant independent predictors of CAD ( P < 0.05 for all) in FH after adjusting for other modifiable risk factors. Conclusions: Elevated Lp(a), hypertension and renal insufficiency are independent risk factors beyond elevated pretreatment LDL-cholesterol which predict CAD in patients with FH. In spite of the cross-sectional design of our study, we propose the need for identifying and managing these abnormalities to reduce excess CAD risk in FH patients. However, this proposal remains to be formally tested in a prospective study.